ANALYSIS OF SOLID WASTE MANAGEMENT STRATEGY IN PELAYANGAN DISTRICT, JAMBI CITY, INDONESIA - Murfid Falih Setyonegoro; Rita Retnowati; Sri Wahyuni (Universitas Pakuan, 2022)
The length of the title is recommended to not exceed twenty words. The abstract should be clear, concise, and descriptive. This abstract should provide a brief introduction to the problem, and objective of the paper, followed by a statement regarding the methodology and a summary of the results. The abstract should end with a comment on the significance of the results or a brief conclusion. Acronyms and citations are discouraged in the abstract. The abstract should not exceed 200 words and be followed by keywords (not more than 5 words or phrases arranged in alphabetical order). Keywords are covering scientific and local names (if any), research themes, and special methods used; and sorted from A to Z. The length of the title is recommended to not exceed fifteen words. The abstract should be clear, concise, and descriptive. This abstract should provide a brief introduction to the problem, and objective of the paper, followed by a statement regarding the methodology and a summary of the results. The abstract should end with a comment on the significance of the results or a brief conclusion. Acronyms and citations are discouraged in the abstract. The abstract should not exceed 200 words and be followed by keywords.